THE EFFECT OF JOB SATISFACTION, MOTIVATION AND ORGANIZATIONAL COMMITMENT TO THE PERFORMANCE OF THE PROCUREMENT EXPERTS IN THE INDONESIAN HOUSE OF REPRESETATIVE - Zahera Mega Utama (Program Studi S3 Ilmu Manajemen, 2017)
The objective of this research has to study the effect of job satisfaction, motivation and organizational commitment on performance or the board of expert staff members of parliament, The research was conducted in Jakarta, and The data had been analyzed using path analysis. The population of this research were 91 person of expert staffs in the Parliament. The questionares of this research had been testing on the 40 expert staff. Therefore by simple randomly. The research finding more as follows : 1. There was positive direct effect of job satisfaction onexpert staffs performance, 2, there was a positive direct effect of motivation on performance of expert staff 3. There was a positive direct effect of organization commitment of expert staff. 4. There was a positive direct effect of organization commitment on performance, 5. There was a positive direct effect of job satisfaction on motivation of expert staff and 6. There was a positive direct effect job satisfaction on organizational commitment Keywords: Expert Staff Performance, Job Satisfaction, work motivation, Organizatinal commitment